Bad gifts, community standards, and the disciplining of Theravāda monks - Borchert, Thomas (Journal of contemporary religion, 2020)
The act of giving is among the most fundamental acts within the Buddhist world, particularly in the Theravāda communities of Southeast Asia. In many of these communities, lay followers give food and other dāna (merit-making gifts), providing monastics with the requisites' that they need to survive. Yet there is relatively little discussion within Buddhist or scholarly communities about what should be given, with formulaic lists representing the majority of discussions about these gifts. However, sometimes, the gifts given to monastics are not always appropriate, even bad. What to do in those cases is not always clear. In this article, I explore the ways in which monks in Thailand and Southwest China think about gifts that are not good. What becomes clear is that, despite the prevailing view that discipline is a universal process based on the vinaya (disciplinary code of Buddhism), monks have different views about what constitutes a bad gift' and what to do about it. I argue that paying attention to bad gifts allows us to see that lay communities have significant voice—although this is often implicit rather than explicit—about what constitutes proper' monastic behavior.